ประสิทธิภาพเชิงกำไรของฟาร์มสุกรมาตรฐานในประเทศไทย - อักษรพันธ์ ประพืด; อิศวิลานนท์ สมพร (Asian Journal of Applied Economics, 2013)
บทคัดย่อ บทความนี้นำเสนอการวิเคราะห์ประสิทธิภาพเชิงกำไรของการเลี้ยงสุกรของฟาร์มมาตรฐานทั้งแบบสมบูรณ์ (เลี้ยงทั้งพ่อแม่พันธุ์ การผลิตลูกสุกร และการขุน) และแบบที่ เลี้ยงเฉพาะสุกรขุน รัฐบาลมุ่งให้ความสำคัญกับการเลี้ยงสุกรฟาร์มมาตรฐานเพื่อยกระดับมาตรฐานการผลิตสุกรของไทยให้สูงขึ้นการศึกษาครั้งนี้ ใช้เทคนิคการวัดประสิทธิภาพเชิงกำไรโดยประยุกต์กับข้อมูลที่ได้จากการสัมภาษณ์ผู้เลี้ยงสุกรฟาร์มมาตรฐาน จำนวน 63 ราย แบ่งเป็นฟาร์มเลี้ยงสุกรแบบสมบูรณ์ 30 ราย และฟาร์มเลี้ยงสุกรขุน 33 ราย ผลการศึกษา พบว่า การเลี้ยงสุกรแบบสมบูรณ์มีประสิทธิภาพเชิงกำไรสูงกว่าการเลี้ยงเฉพาะสุกรขุน โดยปัจจัยการใช้แรงงานในครัวเรือนการใช้โปรแกรมการวิเคราะห์ประสิทธิภาพการผลิต และการมีที่ปรึกษาฟาร์มเป็นตัวแปรที่มีผลต่อประสิทธิภาพเชิงกำไรของฟาร์มทั้งสองระบบ รัฐบาลจึงควรเน้นการใช้มาตรการช่วยเหลือเกษตรกร ในด้านที่เกี่ยวข้องกับปัจจัยดังกล่าวโดยเฉพาะอย่างยิ่งการควบคุมราคาอาหารสัตว์การส่งเสริมทักษะความรู้ และความชำนาญของแรงงานและผู้ประกอบการ รวมถึงการสนับสนุนให้ฟาร์มใช้โปรแกรมคอมพิวเตอร์เพื่อ วิเคราะห์ประสิทธิภาพการผลิตและการได้รับคำปรึกษาในการจัดการระบบฟาร์ม เพื่อเพิ่มประสิทธิภาพเชิงกำไรของการผลิตสุกรทั้งระบบในประเทศ คำสำคัญ: ประสิทธิภาพเชิงกำไร ฟาร์มสุกรมาตรฐาน Abstract This paper determines the profit efficiency of pig production in Thailand. Two standardized farming systems were studied, namely, the farrow to finish production system (which includes breeding, producing piglets and fattening) and the finishing system (which is piglets fattening only).The government is promoting standardized farm to increase the efficiency of the pig industry. The stochastic profit frontier is the main methodology. The survey data of 63 standardized farms comprising 30 farrow to finish farms and 33 finishing farms were used. The results show that the farrow to finish system was more efficient than the finishing system. The factors that significantly affected profit efficiency of both farming systems were: use of family labor, computerization of the farm database and some operations, and consultation with sources of advice and information. These findings suggest that government should provide producers such assistance as feed price control, training of farm workers and managers/owners, encouraging and training farmers to use computer software, and facilitating farm consultation. Keywords: profit efficiency, standardized pig farm, stochastic frontier analysis